Charge Influence on the Nitrogen Molecule Adsorption in Porous Silicon: An Ab Initio Molecular Dynamics Study. Issue 1 (23rd August 2019) - Barrita, Lilia P.; Raga, Micaela J.; Wang, Chumin
Abstract : A first‐principles study on the adsorption of nitrogen atom (N), nitrogen molecule (N2 ), and nitrogen oxides into the hydrogen‐passivated surface of porous silicon (PSi) is presented. This study is conducted within the Car–Parrinello molecular dynamics (MD) framework based on the density functional theory and using a parallelized code developed for the plane‐wave basis with pseudopotentials. The MD results reveal the chemisorption of N atom and of nitrogen dioxide (NO2 ), in contrast to no permanent bonding found for the N2, nitric oxide (NO), and nitrous oxide (N2 O) cases. For the latter, a study of the electric charge effects on the kinetics and chemisorption is performed. The lattice vibrational modes and infrared (IR) absorption spectra are further calculated by means of the density functional perturbation theory. The difference between IR spectra obtained from PSi with and without the adsorbed N2 O molecule reveals its IR‐active modes, which are compared with measured vibrational frequencies of gaseous N2 O. Abstract : An ab initio molecular dynamics study of electric charge ( Q ) effects on the nitrous oxide (N2 O) molecule adsorption in porous silicon is presented, where the configurations after 500 fs, respectively, for negative ( Q = −2 e ), neutral ( Q = 0), and positive ( Q = +2e) charges reveal different chemisorption outcome.